Paco de Lucía and Jazz: Melodic-Harmonic Improvisation as a Central Element in “Zyryab”(1990) - Juan Zagalaz (Analytical Approaches to World Music)
In the past few years, the academic literature on the relationship between jazz and flamenco has grown exponentially. Specialists agree on the importance of Paco de Lucía as the catalyst of the different music languages, who emerged as the figure who opened the door to different approaches that include jazz and flamenco elements. De Lucía’s album “Zyryab,” released in 1990 and including Chick Corea as a guest in the homonymous track, is considered the peak of this contact, in which both musics are blended in a very specific way. This paper focuses on both the compositional approach of de Lucía in the song Zyryab and on his harmonic–melodic soloing, to demonstrate how profound the interculturation process was. It shows that de Lucía took jazz music as an inspiration for the structure of the song Zyryab, by including an introduction, head, and choruses for improvisation. It also shows how Paco de Lucía’s soloing vocabulary works, in which jazz-related resources such as the altered scale, the whole tone, or the octatonic scales are applied over the chord progression, confirming his debt to jazz–soloing methodology.